Starting with the left-hand side:
cosec^2x(tan^2x - sin^2x)
Using the identities:
cosec^2x = 1/sin^2x
tan^2x = sin^2x/cos^2x
We can rewrite the left-hand side as:
1/sin^2x * (sin^2x/cos^2x - sin^2x)
Simplifying:
1/sin^2x * [(sin^2x - sin^2x*cos^2x)/cos^2x]
Expanding the numerator:
1/sin^2x * [sin^2x(1 - cos^2x)/cos^2x]
Using the identity:
1 - cos^2x = sin^2x
1/sin^2x * [sin^2x*sin^2x/cos^2x]
Simplifying:
1/sin^2x * [sin^4x/cos^2x]
Simplifying the fraction:
1/sin^2x * tan^2x
Multiplying fractions:
tan^2x * 1/sin^2x
This simplifies to:
tan^2x/cos^2x
Using the identity tan^2x = sin^2x/cos^2x:
sin^2x/cos^2x
This is equal to the right-hand side, therefore proving that:
cosec^2x(tan^2x - sin^2x) = tan^2x.
Prove that cosec²x(tan²x-sin²x)=tan²x
1 answer